HASIL PEMBERDAYAAN KADER-KESEHATAN-NAGARI MENGGUNAKAN APLIKASI-ANDROID UNTUK MENEMUKAN LANSIA RISIKO TINGGI STROKE TAHUN 2024 - Erdanela Setiawati (Nusantara Hasana Journal, 2025)
Stroke is a non-communicable disease (NCD) that causes death and disability in Indonesia. Half of strokes occur in those over 75 years of age. More than half of the elderly in Indonesia are at high risk (RISTI) for stroke. One effective stroke prevention strategy is to focus on the RISTI population, risk factor management, and implement the use of mobile technology (Electronic Health Information Technology) in health professionals and the general public. There are no trained health cadres in efforts to prevent stroke in the elderly using mobile technology in Nagari-Gurun-Panjang-Utara. Improving the knowledge and skills of village health cadres using the android application "Cegah-Stroke-Erdanela" in finding elderly RISTI-stroke. Community Empowerment is carried out using the Education and Training method, carried out face-to-face and through WhatsApp groups, implemented in Nagari Gurun Panjang Utara, Bayang District, South Coast Regency, West Sumatra Province in August 2024. Partners are 10 village health cadres. Cadre knowledge is measured using pre-test and post-test questionnaires, while cadre skills are measured by observation using a checklist. Data analysis is descriptive and presented with narratives, tables and pictures. The knowledge of village health cadres using the android application to find elderly RISTI-stroke, increased by 5.70. Village health cadres who are skilled at using the application properly and correctly at the end of the training were 90%. Education and Training have succeeded in increasing the knowledge and skills of village health cadres in using the android application to find elderly RISTI-stroke in an effort to prevent stroke.